2010
DOI: 10.1007/s12223-010-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Decisive role of lipopolysaccharide in activating nitric oxide and cytokine production by the probiotic Escherichia coli strain Nissle 1917

Abstract: Effects of Gram-negative probiotic E. coli strain Nissle 1917 (EcN) on the production of nitric oxide (NO) and cytokines were determined in cultures of resident peritoneal cells of rats. The cells (2 x 10(6)/mL) were cultured for 24 h in the presence of live EcN suspension (EcN-Susp), bacteria-free supernatant of this suspension (Sup-EcN), and LPS of EcN origin (LPS-EcN). The biosynthesis of NO was substantially enhanced using live bacteria counts as low as 10(3)/mL applied in the form of EcN-Susp. The same NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Multiple anti-inflammatory characteristics of bacterial factors have been described. Escherichia coli Nissle 1917 (EcN) SN stimulated the secretion of the anti-inflammatory cytokines interleukin (IL)-10 and IL-6, 20 in peritoneal cells of rats, while factors released by Lactobacillus casei Shirota inhibited indomethacin-induced nuclear factor kappa B (NFκB) activation and increases in tumor necrosis factor (TNF)-α mRNA expression. 21 The anti-inflammatory properties were attributed to the bacteria-derived lipopolysaccharide and lactic acid production for EcN SN and L. casei Shirota, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple anti-inflammatory characteristics of bacterial factors have been described. Escherichia coli Nissle 1917 (EcN) SN stimulated the secretion of the anti-inflammatory cytokines interleukin (IL)-10 and IL-6, 20 in peritoneal cells of rats, while factors released by Lactobacillus casei Shirota inhibited indomethacin-induced nuclear factor kappa B (NFκB) activation and increases in tumor necrosis factor (TNF)-α mRNA expression. 21 The anti-inflammatory properties were attributed to the bacteria-derived lipopolysaccharide and lactic acid production for EcN SN and L. casei Shirota, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…21 The anti-inflammatory properties were attributed to the bacteria-derived lipopolysaccharide and lactic acid production for EcN SN and L. casei Shirota, respectively. 20,21 Similar to EcN SN, Bacillus coagulans secreted factors have been reported to promote IL-10 expression, and inhibit oxidative stress-induced formation of reactive oxygen species (ROS). 22 The bacterial strain Lactobacillus fermentum BR11 (BR11) has previously demonstrated probiotic properties in the setting of experimentally-induced colitis.…”
Section: Resultsmentioning
confidence: 99%
“…This results in severe damage to the cell structures and may lead to a variety of pathological diseases including carcinogenesis in humans (44). We found that (45). NO was reported to decrease the oxidation stress mediated by ROS during physiological metabolism in mammalian cells (46).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the immune response of the LPS was mainly induced by the lipid A moiety [23]. Similarly, the LPS from outer membrane of E. coli Nissle 1917 has been reported to elicit pro-inflammatory cytokine IL-1β, IL-6, TNF-α and VEGF production [4,59]. However, E. coli Nissle 1917 metabolites have been shown to reduce proinflammatory cytokine, but nevertheless induced antiinflammatory cytokine [6], whereby the LPS of E. coli Nissle 1917 strain exhibited immunomodulating properties without showing immunotoxin effects [52].…”
Section: Discussionmentioning
confidence: 99%